One holy, catholic and apostolic church: some Lutheran and ecumenical perspectives ; [conference held in June 2008 at the Bossey Ecumenical Institute] - Großhans, Hans-Peter (LWF studies, 2009)
I. An overall inerpretation. Belief in the one holy, catholic and apostlic Church / Eberhard Jüngel -- II. The soteriological relevance of the church : the New Testament witness. The correlation between ecclesiology and soteriology in the New Testament / Eve-Marie Becker -- III. Learning from different Christian traditions and ecumenical dialogues. The ecumenical relevance of the marks of the church / Minna Hietamäki -- The one holy, catholic and apostolic church according to John Calvin / Michel Grandjean -- A harbor for the world in stormy times : ecclesiological reflections in the Orthodox Church and theology / Dimitrios Moschos -- Reconsidering Roman Catholic ecclesiology / Johanna Rahner -- Revisiting Baptist ecclesiology in the context of Myanmar / Samuel Ngun Ling -- Particular, universal, spiritual : understanding the church by drawing on Martin Luther / Philipp Stoellger -- IV. Analyzing ecclesial realities in select Lutheran churches. Focusing on the mission of the church : Lutheran ecclesiology in Ethiopia / Yonas Yigezu -- The common identity of the churches in Malaysia and Southeast Asia / Song-Mee Chung -- Being a Lutheran church in Brazil / Nelson Kilpp -- The one holy, catholic and apostolic church in the North American context / Cheryl M. Peterson